Striate Artery Infarct After Bilateral Carotid Artery Ligation (BCAL) in a Dog: A Multimodal MRI Study - Komornik, Lukas; Lautenschläger, Ines; Vigani, Alessio; Iannucci, Claudia; Pozzi, Antonio; Wang-Leandro, Adriano; Beckmann, Katrin (Frontiers in Veterinary Science, 2020)
Bilateral carotid artery ligation has been reported as a lifesaving procedure to control severe hemorrhage. However, reports are sparse and little information is available regarding the potential risks associated with this procedure. We report an ischaemic brain infarct as a complication after vascular surgery. A three-year old, male intact border collie was presented for acute onset of forebrain signs five days after bilateral carotid artery ligation. Multimodal brain MRI including morphologic sequences, MR angiography, diffusion- and perfusion-weighted images were performed. MRI revealed a well-defined intra-axial lesion of the left caudate nucleus, with increased T2 and decreased T1 signal intensity and moderate heterogeneous peripheral contrast enhancement. The cerebral blood flow was reduced relative to the contralateral caudate nucleus. Images were consistent with a subacute territorial ischaemic infarct of the left striate artery. Additionally, multiple arterio-arterial anastomosis arising from the vertebral arteries were visible in the angiography sequences. Ischemic infarct due to thromboembolism should be considered as a possible complication associated with bilateral carotid artery ligation. Collateral blood supply can develop as early as five days after surgery.